2006
DOI: 10.1212/01.wnl.0000210527.13661.d1
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance predicts treatment decisional abilities in mild to moderate dementia

Abstract: Objective-To examine the contribution of neuropsychological test performance to treatment decision-making capacity in community volunteers with mild to moderate dementia.Methods-The authors recruited volunteers (44 men, 44 women) with mild to moderate dementia from the community. Subjects completed a battery of 11 neuropsychological tests that assessed auditory and visual attention, logical memory, language, and executive function. To measure decision making capacity, the authors administered the Capacity to C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(104 citation statements)
references
References 37 publications
8
96
0
Order By: Relevance
“…This relative weakness in the cognitive models of appreciation is consistent with findings from prior studies (Dymek et al, 2001;Gurrera et al, 2006), and underscores that appreciation is the consent standard that probably relies most heavily on abilities not fully represented in the neuropsychological armamentarium (Marson et al, 1996). Consequently, performance on appreciation is less well modeled by standard cognitive measures.…”
Section: Predictors Of Medical Decision-making Capacity In MCI 303supporting
confidence: 79%
See 1 more Smart Citation
“…This relative weakness in the cognitive models of appreciation is consistent with findings from prior studies (Dymek et al, 2001;Gurrera et al, 2006), and underscores that appreciation is the consent standard that probably relies most heavily on abilities not fully represented in the neuropsychological armamentarium (Marson et al, 1996). Consequently, performance on appreciation is less well modeled by standard cognitive measures.…”
Section: Predictors Of Medical Decision-making Capacity In MCI 303supporting
confidence: 79%
“…With regard to MDC, such studies can alert clinicians to specific cognitive impairments threatening consent capacity in MCI. In turn, these findings can facilitate the development of enhanced consent procedures for persons with MCI (Gurrera et al, 2006;Marson et al, 1996;Mittal et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our results also showed that expressing a choice was not related to the other abilities; it was only related to the awareness of the disease. In practice, most mild to moderate patients with AD will be able to express a treatment choice, even if their ability to understand, appreciate or reason is inadequate to support the choice 29 , but patients with AD who had awareness of their overall cognitive function and diagnosis were more likely to be judged competent by physicians 5 . Moreover, the factors related to understanding were reasoning and functional status.…”
Section: Discussionmentioning
confidence: 99%
“…Among the four abilities, understanding is the most stringent consent standard, as it requires comprehension of factual knowledge and understanding of the treatment situation and choices 1,4,6,29 . In previous studies, it has been observed that competence to consent to treatment was especially impaired in patients with AD 5 when cognitive functioning had significantly low scores 29 . The functional status is probably related to understanding because people with lower functional status may be less stimulated and this may hinder comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…This would surely burden people with dementia and affect the results of an assessment with the MacCAT-T. Thirdly, the verbal retrieval factor was based on the factorial analysis of Gurrera et al (2006), but was modified for this study. While the original verbal retrieval factor used the immediate and delayed logical memory subtests (Wechsler, 1997) in addition to the Boston Naming Test, we used the Word List Memory (immediate memory) and Word List Recall (delayed memory) subtests of the CERAD-NP.…”
Section: Limitations Of the Studymentioning
confidence: 99%